Interleukin-4 Receptor Alpha-Deficient BALB/c Mice Show an Unimpaired T Helper 2 Polarization in Response to Leishmania major Infection - Mohrs, Markus (American Society for Microbiology, 2000)
We recently generated interleukin-4 (IL-4) receptor alpha-deficient (IL-4Rα(−/−)) BALB/c mice and showed evidence for a protective role of IL-13-mediated functions in leishmaniasis. In this study, we investigated the IL-4 expression and T helper 2 (Th2) development in Leishmania major-infected IL-4Rα(−/−) mice. Here we show that the early burst of IL-4 expression observed in L. major-infected BALB/c mice is independent of IL-4Rα-mediated functions. Subsequently, we confirmed an impaired Th2 development in vitro. Unexpectedly, during L. major infection, isolated CD4(+) IL-4Rα(−/−) T cells expressed high IL-4- but low gamma interferon (IFN-γ)-specific mRNA, comparable to Th2-polarized BALB/c CD4(+) cells and in contrast to Th1-polarized C57BL/6 CD4(+) cells. Since antigen-specific restimulated popliteal lymph node cells (PLN) of IL-4Rα(−/−) mice also responded with high IL-4 but low IFN-γ production, comparable to Th2-polarized cells from wild-type BALB/c mice and in contrast to Th1-polarized C57BL/6 cells, these results suggested an unimpaired Th2 polarization during an established infection with L. major. To further define the observed IL-4 receptor-independent Th2 cell phenotype, we determined an independent Th2 marker, the IL-12 receptor beta-2 (IL-12Rβ2)-specific transcript levels of CD4(+) T cells. Confirming Th2 polarization in L. major-infected IL-4Rα(−/−) mice, comparable IL-12Rβ2 message levels between CD4(+) T cells from infected IL-4Rα(−/−) mice and Th2 cells from BALB/c mice were found, whereas Th1-polarized C57BL/6 cells showed strikingly increased IL-12Rβ2 expression levels. These results indicate that signals mediated by the IL-4Rα are not necessary to induce and sustain an efficient IL-4 expression and Th2 polarization in L. major-infected BALB/c mice and suggest that IL-4Rα-independent mechanisms underlie the default Th2 development in L. major-infected BALB/c mice.